1993
DOI: 10.1002/ccd.1810300315
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of undeployed stents from the right coronary artery: report of two cases

Abstract: Two patients are described in whom an undeployed stent (1 Wiktor and 1 Palmaz-Schatz) was retained in the proximal segment of the right coronary artery during coronary angioplasty. In both cases the stent was caught by a technique using a second guidewire. The stent was removed in the first patient during bypass surgery; in the second patient it was removed from the femoral sheath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Kobayashi et al [3] have written about their successful retrieval of a PS stent with the gooseneck snare device from the left main coronary artery. Other authors have reported on a special two-wire technique that allows retrieval of the coronary stents without any complications [5] or fixation and removal of the undeployed stents during CABG or from the sheath in the femoral artery, respectively [6]. Further applications include balloon inflation distal to the stent [7] as well as the use of a low-profile balloon catheter together with 6 Fr biopsy forceps to catch and pull back a lost stent from the descending aorta [8].…”
Section: Discussionmentioning
confidence: 98%
“…Kobayashi et al [3] have written about their successful retrieval of a PS stent with the gooseneck snare device from the left main coronary artery. Other authors have reported on a special two-wire technique that allows retrieval of the coronary stents without any complications [5] or fixation and removal of the undeployed stents during CABG or from the sheath in the femoral artery, respectively [6]. Further applications include balloon inflation distal to the stent [7] as well as the use of a low-profile balloon catheter together with 6 Fr biopsy forceps to catch and pull back a lost stent from the descending aorta [8].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, currently, interventional techniques are often used before surgery. One of these techniques is advancing another guidewire throughout stent filaments and squeezing the dislodged stent into the vessel wall before the guidewire is retrieved carefully (5). Another technique is also advancing another guidewire outer region of the stent and squeezing the dislodged stent into the vessel wall by inflating the balloon and retrieving the material similar to Fogarty's method (6).…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary embolization of balloon-mounted stents is a serious complication associated with a high risk of coronary thrombosis and subsequent myocardial infarction [4][5][6][7]. Bailout cardiac surgery may be indicated if percutaneous retrieval attempts fail [8,9].…”
Section: Discussionmentioning
confidence: 99%